ANALISIS KUALITAS FISIK BRIKET BIOARANG DARI LIMBAH THE DENGAN PEREKAT ORGANIK - Dwi Hastuti, Sintawati; Ulinna’mah, Lady Itsnia; Kurniawan, Anri (Jurnal Agritechno, 2025)
Tea plants produce waste consisting of stems, leaves, and tea dregs. Tea stems are waste from the pruning process, tea leaves do not meet processing standards, and tea dregs are produced after brewing beverages. Tea plant waste, which is biomass, can be used as an alternative energy source in the form of biochar briquettes for cooking fuel. High-quality briquettes are defined according to SNI standard number 01-6235-200 with the following criteria: moisture content of less than 8%, ash content of less than 6%, and a calorific value of 500 cal/gram. Good biochar briquettes are characterized by ease of ignition during burning and stable combustion at a temperature of 350°C for a long time. The production process includes cleaning, drying, carbonization, sieving, preparing adhesive, mixing charcoal with adhesive, molding, and producing biochar briquettes. Testing is conducted to evaluate ease of ignition (s), burning duration (s), moisture content (%), ash content (%), and calorific value (cal/gram). Data analysis is carried out using a single-factor Analysis of Variance (ANOVA) method with Microsoft Excel and SPSS 27, based on a Completely Randomized Design (CRD) with 35 total samples. According to laboratory results, there were no significant differences in quality indicators such as ease of ignition (s), burning duration (s), moisture content (%), ash content (%), and calorific value (cal/gram), as the F critical value exceeded the actual F value, and the P-value was greater than 0.05. Biochar briquettes made from tea stems, leaves, and dregs meet the criteria based on ANOVA test results, with no significant differences found. Nevertheless, all data indicate that the biochar briquettes produced are of high quality in accordance with the SNI standard, making them suitable for use on a household scale.